Cytokine Profile in Striated Muscle Laminopathies: New Promising Biomarkers for Disease Prediction - Cristina Cappelletti (Cells, 2020)
Laminopathies are a wide and heterogeneous group of rare human diseases caused by mutations of the LMNA gene or related nuclear envelope genes. The variety of clinical phenotypes and the wide spectrum of histopathological changes among patients carrying an identical mutation in the LMNA gene make the prognostic process rather difficult, and classical genetic screens appear to have limited predictive value for disease development. The aim of this study was to evaluate whether a comprehensive profile of circulating cytokines may be a useful tool to differentiate and stratify disease subgroups, support clinical follow-ups and contribute to new therapeutic approaches. Serum levels of 51 pro- and anti-inflammatory molecules, including cytokines, chemokines and growth factors, were quantified by a Luminex multiple immune-assay in 53 patients with muscular laminopathy (Musc-LMNA), 10 with non-muscular laminopathy, 22 with other muscular disorders and in 35 healthy controls. Interleukin-17 (IL-17), granulocyte colony-stimulating factor (G-CSF) and transforming growth factor beta (TGF-β2) levels significantly discriminated Musc-LMNA from controls; interleukin-1β (IL-1β), interleukin-4 (IL-4) and interleukin-8 (IL-8) were differentially expressed in Musc-LMNA patients compared to those with non-muscular laminopathies, whereas IL-17 was significantly higher in Musc-LMNA patients with muscular and cardiac involvement. These findings support the hypothesis of a key role of the immune system in Musc-LMNA and emphasize the potential use of cytokines as biomarkers for these disorders.